2190. Characterization of Inhaled Nitric Oxide (iNO) for the treatment of Viral Community Acquired Pneumonia (CAP). (15th December 2022) - Tal, Asher; Shifer, Yehonatan; Wolak, Talya; Grossman, Alon; Dicker, Dror
Abstract: Background: Nitric Oxide (NO) has been previously demonstrated to have antimicrobial, anti-inflammatory, and vasodilator properties. Extensive work has been done in the clinical setting to explore these properties with iNO administered intermittently at high concentrations of 150-250 ppm. While viral CAP has gained major attention with the emergence of COVID-19, treatment methods remain limited and are challenging to develop. The purpose of this study is to assess iNO treatment administered to hospitalized adults with viral CAP. Methods: This is a randomized, open label multi-center ongoing study. Study population includes subjects aged 18-80, hospitalized for vCAP including COVID-19. Following enrollment, subjects were randomized 1:1 to either iNO [150ppm for 40 minutes, 4 times daily, up to 7 days in addition to standard supportive treatment (SST)], or control [SST alone]. iNO was delivered by LungFit TM, an innovative NO generator under development (Beyond Air, NY, USA). Follow up period is 180 days. Study endpoints include safety and the time to reach a stable saturation of ≥93%. In addition, different other clinical parameters are collected to profile the effect of iNO in this population. Results: Analyzing the Intent To Treat (ITT) population (n=35, [16 iNO and 19 control]), safety profile of iNO treatment observed so far, was found to be favorable with no treatment related Adverse Events (AEs). Faster clinical improvement was noted in the iNO treatment group, paralleling CRP improvement between baseline to end of treatment (mean 2.7 mg/dl comparing treatment group [n=8] to control group [n=7], data not final). Conclusion: These data suggest that intermittent treatment with 150ppm iNO is safe and well tolerated and may contribute to faster clinical improvement in viral CAP. Different laboratory parameters may shed some light and help to characterize this observed effect, supporting the further exploration of iNO for the treatment of viral lower respiratory tract infection, including COVID-19. Preliminary findings were presented at ECCMID 2022 Disclosures: Asher Tal, MD, Beyond Air Inc: Advisor/Consultant|Beyond Air Inc: Stocks/Bonds Talya Wolak, MD, talya wolak: Advisor/Consultant Dror Dicker, MD, AstraZenca: Advisor/Consultant|AstraZenca: Honoraria|Beyond Air: Grant/Research Support|Boehringer Ingelheim: Advisor/Consultant|Boehringer Ingelheim: Honoraria|Eli Lilly: Grant/Research Support|Novo Nordisk: Advisor/Consultant|Novo Nordisk: Grant/Research Support|Novo Nordisk: Honoraria.